Differentiate
(4x-1) * (4x-1)^0.5
I think im meant to use the product formula? But it doesn't work when i used it =(
Any help would be appreciated . Ty
Why do you blame the Product Rule?
(4x-1) * (4x-1)^0.5
First, the easy way.
(4x-1) * (4x-1)^(1/2) = (4x-1)^(3/2)
(d/dx)[(4x-1)^(3/2)] = [(3/2)*(4x-1)^(1/2)]*4 = 6*(4x-1)^(1/2)
Now the Product Rule
(d/dx)[(4x-1) * (4x-1)^(1/2)] = (4x-1)*(1/2)*[(4x-1)^(-1/2)]*4 + [(4x-1)^(1/2)]*4
= 2*(4x-1)^(1/2) + 4*(4x-1)^(1/2) = 6*(4x-1)^(1/2)
That looks very similar to the other version.